2016
DOI: 10.15405/epsbs.2016.11.20
|View full text |Cite
|
Sign up to set email alerts
|

Students’ and Professors’ Perception of Occurrence and Disturbance of Disruptive Classroom Behaviors

Abstract: Disruptive behavior could be defined as the behavior that interrupts the educational process and causes stress to teachers or other students. In this research an anonymous questionnaire containing 30 disruptive behaviors was given to a group of students (N=251) and professors (N=49) at the University of Applied Sciences VERN' (Zagreb, Croatia). Participants had to appraise: a) to what extent those behaviors occur in the classroom and b) how disturbing they are. Results have shown that disruptive behaviors occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…One of the reasons for disruptive behavior can be the challenges faced by both faculty and students to accustom to the new learning environment 19 . Multiple studies have reported the prevalence of incivility along with strategies to prevent this in face‐to‐face learning 2,3,5,20–22 . To our knowledge no study has been carried out to assess the prevalence, and characteristics of IOLE from dental students and faculty perceptive.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the reasons for disruptive behavior can be the challenges faced by both faculty and students to accustom to the new learning environment 19 . Multiple studies have reported the prevalence of incivility along with strategies to prevent this in face‐to‐face learning 2,3,5,20–22 . To our knowledge no study has been carried out to assess the prevalence, and characteristics of IOLE from dental students and faculty perceptive.…”
Section: Introductionmentioning
confidence: 99%
“…19 Multiple studies have reported the prevalence of incivility along with strategies to prevent this in face-to-face learning. 2,3,5,[20][21][22] To our knowledge no study has been carried out to assess the prevalence, and characteristics of IOLE from dental students and faculty perceptive. The rationale of this study was to improve the quality of online learning by understanding the perception of online incivility by undergraduate dental students and faculty.…”
Section: Introductionmentioning
confidence: 99%